"Marginalized Islam": the transfer of rural rituals into urban and pluralist contexts and the emergence of transnational "communities of practice" - Langer, Robert (Ritual matters, 2012)
The Islamic Studies/Ottoman Studies sub-project of the Collaborative Research Center ‘Dynamics of Ritual’ at Heidelberg University focuses on formerly so-called ‘heterodox’ groups of Islamic origin. These groups emerged in the late middle ages and early modern times in the region around Upper Mesopotamia, reaching out into Southern Caucasia and Western Iran. Upper Mesopotamia was from the sixteenth century onwards part of the Ottoman Empire.1 The region nowadays comprises Central and Eastern Anatolia, Northern Syria and Iraqi Kurdistan. Modern migrations brought the ritual practice of heterodox Muslim groups form the rural Near East into its urban centres — such as I . stanbul or Ankara — and even further to Western Europe. In the course of this development and in connection with high degrees of mobility, communication and media representation (especially the medialisation of rituals), diaspora groups of Islamic origin developed transnational ‘communities of practice’2 comprising the diaspora communities, the groups in urban centres of the Near East, as well as the remaining village communities in the regions of origin. This essay deals mainly with the Alevis from Turkey and aims to exemplify some aspects of the concept of ‘transfer of ritual’, which was developed at Heidelberg as an analytical means to analyse the relation between transformations of rituals and changing contexts of cultural performances.